Solid-Liquid Separation Properties of Thermoregulated Dicationic Ionic Liquid as Extractant of Dyes from Aqueous Solution - Rui Lv; Shuya Cui; Yangmei Zou; Li Zheng (Journal of Analytical Methods in Chemistry)
Two thermoregulated dicationic ionic liquids were synthesized and applied for effective extraction of the common dye malachite green oxalate (MG). The extraction parameters such as amount of ionic liquids, pH of water phase, extraction time, cooling time, and centrifugal time on the extraction efficiency were investigated systematically. It revealed that the dye has been successfully extracted into the ionic liquids, with high extraction efficiency higher than 98%, and recovery of 98.2%–100.8%, respectively. Furthermore, these ionic liquids can be recycled easily after elution. The reusable yields were 87.1% and 88.7%. The extraction of the dye into the thermoregulated ionic liquid provides a method of minimizing pollution of waste water potentially.